THE REPRESENTATIONS OF TOXIC MASCULINITY IN THINGS FALL APART (1959) - Muhlisin Muhlisin; Agus Syahid (Sunan Kalijaga State Islamic University Yogyakarta, 2025)
Toxic masculinity refers to certain masculine behaviors and traits that can have adverse effects on both men and those around them. This study aimed to identify the concept of masculinity, forms, causes, and impacts of toxic masculinity on the protagonist, Okonkwo, and those around him in Chinua Achebe’s Things Fall Apart, based on Connell’s hegemonic masculinity theory. This qualitative study employed a textual analysis method and a close reading approach. The primary data for this study were drawn from the novel Things Fall Apart. The results indicated that in Igbo culture, masculinity is defined by the man’s role as the primary leader and decision-maker within the family unit. Okonkwo exhibits several forms of toxic masculinity, including physical violence, dominance over women, misogyny, coercion, and homicide. Various factors, such as a dysfunctional family, exposure to violence, peer rejection, bullying, fear of weakness, and fear of failure influenced Okonkwo’s behaviors. As a consequence, he suffered from depression, anxiety, and encouragement to violence, which ultimately led him to be aggressive to those around him, and this culminates in his suicide.